A critical assessment of anti‐corruption strategies for economic development in sub‐Saharan Africa. (14th May 2020) - Senu, Oluwafemi
Abstract: Motivation: Many countries in sub‐Saharan Africa (SSA) experience thwarted economic development and corrupt public administration. As the United Nations Convention Against Corruption (UNCAC) focuses on implementation mechanisms in SSA, there is a need to examine the causes of the setbacks affecting these mechanisms, looking at the current trends of corruption and their impact on socioeconomic development. Purpose: This article focuses on assessing setbacks in anti‐corruption strategies to advance economic development in SSA, primarily looking at how and in what conditions UNCAC prevents corruption and manages responses in SSA. Approach: This article adopts a descriptive and an explanatory perspective, using case studies of Kenya and Nigeria to explain and show how far the objectives of anti‐corruption strategies have been met, and assessing the causes of setbacks. In this context, the article also explores the challenges facing the UK's Department for International Development (DFID). Conclusions: Socioeconomic development in SSA is hard to separate from maladministration and large‐scale corruption. The findings reveal the gravity of this impact and its interrelated factors of "active" and "benign" corruption. This article concludes that for SSA to create sustainable economic environments, the causes of the failure to stamp out corruption need to be addressed, and dishonesty, maladministration, illicit activities, nepotism curtailed, along with corrupt influences on anti‐corruption legislation. Policy implications: The article concludes that if governance does not prevent the failures of anti‐corruption strategies, an interventionist response will only weaken national endeavours, making it difficult to reach UNCAC's vision of sustainable and corruption‐free economic environments.